Framing VS. Framed: Storyness in Chopin´s "Elizabeth stock´s one story" - Meyers Skredsvig, Kari (Universidad de Costa Rica, 2015)
El siguiente análisis explora las maneras en que diferentes tipos y niveles de estructuras interactúan formando tanto la narración como la construcción del significado en la historia de Chopin. La estructura de la historia anuncia la acción literal de la construcción en el núcleo del argumento, establece parámetros para el proceso cognitivo de la historia y compara la estratégica apropiación de las dos estructuras que hace el sujeto de la enunciación de la historia principal, para contar y hacer valer su historia a su manera. The following analysis explores the ways in which different types and levels of frames interact in structuring both the narration and the construction of meaning(s) in Chopin's story. The frame story foreshadows the literal action of framing at the crux of the plot, establishes parameters for cognitive processing of the story, and parallels the strategic appropriation of both frames by the subject of the enunciation of the main story for both telling and validating her story in her own way.